Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bone.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 positive periosteal cells in fracture repair of the adult mammalian long bone

Abstract: A Sox9 skeletal progenitor population resides in the adult periosteum. Fate tracing studies show that descendants of the Sox9 periosteal progenitors give rise to chondrocytes, osteoblasts and mature cortical osteocytes in repair of the fractured femur. To our knowledge this is the first report of a reparative Sox9 progenitor population in the periosteum of the adult long bone. Taken together with developmental studies, our data suggest a broad role for Sox9 osteochondroprogenitors in development and repair of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 41 publications
6
44
0
Order By: Relevance
“…At day 7, we observe a co-localization of Sox9 and Runx2 (Figure 1B), it can be speculated that co-expression of both transcription factors marks a switch in the genetic program, from uncommitted pre-osteoblasts to chondrocyte differentiation, similar to what has been shown in bone development (45). Alternatively, Sox9 expressing cells might differentiate into osteoblasts, as described previously (42)(43)(44). Our results show close proximity between osteoprogenitors (Runx2 + ) or osteoblasts (Osx + ) and CD31 + endothelium (Figures 1C,D).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At day 7, we observe a co-localization of Sox9 and Runx2 (Figure 1B), it can be speculated that co-expression of both transcription factors marks a switch in the genetic program, from uncommitted pre-osteoblasts to chondrocyte differentiation, similar to what has been shown in bone development (45). Alternatively, Sox9 expressing cells might differentiate into osteoblasts, as described previously (42)(43)(44). Our results show close proximity between osteoprogenitors (Runx2 + ) or osteoblasts (Osx + ) and CD31 + endothelium (Figures 1C,D).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, these progenitor cells either express Sox9 or Runx2, which are regulated by direct repression of the opposing pathway (via β-catenin expression) and define further differentiation into chondrocytes or osteoblasts, respectively (41). However, several studies show the importance of Sox9 expressing progenitor cells that support mineralization and osteogenesis within the fracture gap (42)(43)(44). At day 7, we observe a co-localization of Sox9 and Runx2 (Figure 1B), it can be speculated that co-expression of both transcription factors marks a switch in the genetic program, from uncommitted pre-osteoblasts to chondrocyte differentiation, similar to what has been shown in bone development (45).…”
Section: Discussionmentioning
confidence: 99%
“…In response to long bone fracture, periosteal‐derived cells form a cartilaginous callus external to the cortical bone that bridges the fracture gap and functions as an endochondral template for the formation of the bony callus . The osteoprogenitors that give rise to the hard callus are also derived from the periosteum, and there is evidence suggesting the presence of an osteochondroprogenitor stem cell in the periosteum . In this regard, bone regeneration in response to fracture injury involves a coordinated response of periosteal cells to bridge the fracture and restore function.…”
mentioning
confidence: 99%
“…We then turned our attention to the origins and cell fates of the progenitor cells contributing to fracture repair at these three sites. Previous studies demonstrated that the periosteum is a primary source of progenitor cells contributing to fracture repair . A subset of cells in the periosteum express Prx1 and preferentially differentiate into osteogenic and/or chondrogenic lineages in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture repair recapitulates the process of embryonic development with the coordinated participation of a number of cell types . Several potential sources of skeletal stem cells/progenitors have been reported including endosteum, periosteum, bone marrow,and adjacent soft tissues . Among these sources, periosteum and bone marrow have been identified as main sources of progenitors for fracture repair .…”
Section: Introductionmentioning
confidence: 99%